2020
DOI: 10.1021/acscatal.0c00818
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Alcohols as Rechargeable Electrofuels: Electrooxidation of Isopropyl Alcohol at Pt Electrodes

Abstract: Fuel cells can be operated directly by oxidation of isopropyl alcohol (IPA) to acetone (ACE). If the product ACE is hydrogenated, IPA is formed again. In this way, IPA serves as a rechargeable electrofuel. In this work, we study the oxidation of IPA at Pt electrodes using several complementary experimental methods, including cyclic voltammetry (CV), electrochemical real-time mass spectrometry (EC-RTMS), and electrochemical infrared reflection absorption spectroscopy (EC-IRRAS), in combination with density func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
63
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 74 publications
14
63
1
1
Order By: Relevance
“…By irradiation of the rutile substrates, a negative band appears at 1712 cm –1 , which can be assigned to the CO stretching mode of acetone. , This band intensifies with increasing irradiation time. As all spectra are difference spectra, negative bands (downward oriented) indicate species that are formed, while positive bands (upward oriented) correspond to species that are consumed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…By irradiation of the rutile substrates, a negative band appears at 1712 cm –1 , which can be assigned to the CO stretching mode of acetone. , This band intensifies with increasing irradiation time. As all spectra are difference spectra, negative bands (downward oriented) indicate species that are formed, while positive bands (upward oriented) correspond to species that are consumed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Under different excitation wavelengths, the product yields were quite close to that of a non-irradiated reaction ( Table S6 ). This result can be explained by the fact that isopropanol is a stronger reducing agent (E o of acetone/isopropanol is around 0.76 V vs SHE) ( Waidhas et al., 2020 ) than Pd (E o of Pd(II)/Pd(0) is around 0.92 V vs SHE) ( Bratsch, 1989 ), and that the holes are quenched by isopropanol before they can catalyze the formation of R-Pd II -X intermediate. To address the concern of homocoupling of phenylboronic acid ( Adamo et al., 2006 ) that could be catalyzed by the hot holes ( Gellé et al., 2020 ) or bromobenzene to the biphenyl, a series of control experiments using only either reactant showed undetected product under various irradiation conditions ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…[52,53] However, adsorbed CO is not present on platinum during the oxidation of 2-propanol and the reaction is selective to acetone without any dissociation products detected. [36] Given the absence of limitations from adsorbed CO, the beneficial effect of ruthenium in enhancing the 2-propanol oxidation must be of different origin. Indeed, well-controlled rotating disk electrode (RDE) experiments with commercial Pt x Ru 1-x /C catalysts have shown that the presence of ruthenium gives rise to an unusual early oxidation process at potentials around þ0.15 V RHE (i.e., close to the equilibrium potential of the 2-propanol/acetone couple) which determines the OCV in DIFCs using PtRu/C anodes.…”
Section: Pt and Ptrumentioning
confidence: 99%
“…Acetone is the primary product of 2-propanol oxidation with a selectivity of almost 100% with platinum-based catalysts. [32][33][34][35] This originates from the fact that secondary alcohols such as 2-propanol do not adsorb dissociatively, [36][37][38][39] whereas also the product acetone remains molecularly intact when adsorbed, except for Pt(100) terraces. [40] Hence, the difficulty in splitting of the C-C bond of secondary alcohols leads to the absence of adsorbates (such as CO) that would be fully oxidized to CO 2 .…”
Section: Introductionmentioning
confidence: 99%